Comparing the Effectiveness of Three Strategies in Teaching Selected Topics in Mathematics on the Students’ Achievement in and Attitude toward Mathematics - Pantolla, Judy Mae G. (Journal of International Scholars Conference - EDUCATION/SOCIAL SCIENCES, 2016)
Three strategies in teaching Mathematics were implemented to First Year students of LPNHS-Main during the Third Grading Period S.Y. 2011-2012. A Quasi- Experimental Design was used to compare the effectiveness of the three strategies. The data were analyzed using independent and dependent sample t-test and ANCOVA to test the significant difference of means from the three groups. The results revealed that there is a significant difference in the pretest and post test mean scores in the achievement of each group, most remarkable in the group that was exposed to the manipulative materials. This shows that the use of Manipulative materials is the most effective strategy in terms of improving achievement of the student and it is followed by the Cooperative learning strategy while the Chalk-board and talk strategy is the least effective. Another key finding in this paper is that each of the three strategies has noteworthy weakness in at most one category in the attitude inventory. These are the students who were exposed in Chalk-board and talk strategy, had their personal confidence about Mathematics seemingly decreased. Similarly, those who undergone the Cooperative Learning strategy had their interest toward the usefulness of Mathematics apparently lessened and lastly, the group exposed in Manipulative materials appears to have their perception about the teacher’s attitude in terms the care and concern with them also diminished.